The relationship between dioxin-like polychlorobiphenyls and IGF-I serum levels in healthy adults: evidence from a cross-sectional study. - Octavio P Luzardo (Public Library of Science (PLoS), 2012)
Objective Insulin-like growth factor I (IGF-I) and dioxin-like polychlorobiphenyls (DL-PCBs) have been associated with the pathogenesis of several diseases like cancer, diabetes and growth disorders. Because it has been suggested that organohalogenated contaminants could influence IGF-I levels in adults, the potential relationship between DL-PCBs and IGF-I serum levels was studied in 456 healthy adults from a representative sample of the general population of the Canary Islands (Spain). Design Free circulating serum levels of IGF-I and IGFBP-3 were measured through an ELISA methodology, while the serum levels of the 12 DL-PCBs congeners (IUPAC numbers # 77, 81, 105, 114, 118, 123, 126, 156, 157, 167, 169, and 189) were measured by gas chromatography/mass spectrometry (GC-MS). Results DL-PCBs 156 and 167, Total DL-PCBs body burden (∑PCBs: sum over the 12 measured DL-PCBs), and Total toxic burden (in terms of toxic equivalence to dioxins: ∑TEQs) showed a trend of inverse association with IGF-I serum levels in the whole studied population. After adjusting for potential confounders, including gender, body mass index (BMI), age, and IGF-binding protein-3 (IGFBP-3), younger (18-45 years) women with lower BMI (<27 kg/m(2)) and detectable levels of DL-PCB-156 showed significantly lower IGF-I levels than those in the same age and BMI subgroup with non-detectable levels of DL-PCB-156 (p<0.001). Similarly, ∑PCBs and ∑TEQs showed a tendency to an inverse association with IGF-I levels in the same group of women (p=0.017 and p=0.019 respectively). Conclusions These findings suggest that DL-PCBs could be involved in the regulation of the IGF-system in a way possibly influenced by gender, age and BMI. Although these results should be interpreted with caution, such circumstances could contribute to explain the development of diseases associated to the IGF system.